2005
DOI: 10.1016/j.trstmh.2004.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Pan-African polyspecific antivenom produced by caprylic acid purification of horse IgG: an alternative to the antivenom crisis in Africa

Abstract: A polyspecific Pan-African antivenom has been produced from the plasma of horses immunized with a mixture of the venoms of Echis ocellatus, Bitis arietans and Naja nigricollis, the three most medically important snakes in sub-Saharan Africa. The antivenom is a whole IgG preparation, obtained by caprylic acid precipitation of non-IgG plasma proteins. The antivenom effectively neutralizes the most important toxic activities of the three venoms used in the immunization in standard assays involving preincubation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 25 publications
6
96
1
Order By: Relevance
“…51 Bleeding and coagulopathy are the most important systemic pathophysiological manifestations of these envenomings, creating the risk of provoking hemorrhagic strokes, haemodynamic disturbances, cardiovascular collapse, and disseminated intravascular coagulation. 4 Thus, the effective immunodepletion of SVMPs and serine proteinases by the EchiTAb-Plus-ICP antivenom correlates well with our earlier reports of the preclinical venom-neutralizing effectiveness of this antivenom against these important African vipers (using assays of venom-induced lethality, hemorrhage, and coagulation 19,20 and its clinical efficacy in treating human victims of E. ocellatus envenoming. 27 The partial immunological reactivity to some PLA 2 s, disintegrins, and proteinase inhibitors revealed the presence of low affinity or low abundance of antibodies against these components in the antivenom.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…51 Bleeding and coagulopathy are the most important systemic pathophysiological manifestations of these envenomings, creating the risk of provoking hemorrhagic strokes, haemodynamic disturbances, cardiovascular collapse, and disseminated intravascular coagulation. 4 Thus, the effective immunodepletion of SVMPs and serine proteinases by the EchiTAb-Plus-ICP antivenom correlates well with our earlier reports of the preclinical venom-neutralizing effectiveness of this antivenom against these important African vipers (using assays of venom-induced lethality, hemorrhage, and coagulation 19,20 and its clinical efficacy in treating human victims of E. ocellatus envenoming. 27 The partial immunological reactivity to some PLA 2 s, disintegrins, and proteinase inhibitors revealed the presence of low affinity or low abundance of antibodies against these components in the antivenom.…”
Section: Discussionsupporting
confidence: 85%
“…However, keep in mind that immunodepletion does not necessarily imply therapeutic neutralization of these venoms and, therefore, antivenomic analysis has to be complemented by preclinical neutralization studies, followed by appropriate clinical trials. In this respect, preclinical studies with the venoms analyzed in this work performed with EchiTAb-Plus-ICP , 20 showed that this antivenom neutralizes the most clinically relevant toxic (lethal, hemorrhagic, coagulant, and necrotizing) activities of these venoms, 19,20 and also of the venoms of other medically important sub-Saharan African species, i.e., E. leucogaster , E. pyramidum leakeyi , B. gabonica , B. rhinoceros , and B. nasicornis . 20 We conclude, therefore, that partially immunodepleted toxins may not compromise the in vivo neutralizing efficacy of EchiTAb-Plus-ICP antivenom.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations